2009
DOI: 10.1097/chi.0b013e31819176e4
|View full text |Cite
|
Sign up to set email alerts
|

Threat-Related Selective Attention Predicts Treatment Success in Childhood Anxiety Disorders

Abstract: Objective: The present study examined whether threat-related selective attention was predictive of treatment success in children with anxiety disorders and whether age moderated this association. Specific components of selective attention were examined in treatment responders and nonresponders. Method: Participants consisted of 131 children with anxiety disorders (aged 8Y16 years), who received standardized cognitive-behavioral therapy. At pretreatment, a pictorial dotprobe task was administered to assess sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 51 publications
5
51
2
Order By: Relevance
“…Consistent with previous studies, attention to threat on this visual, implicit task seemed to predict limited benefits of CBT [16,18]. As learning is adversely affected by heightened arousal [30], threat perception (and attendant increased arousal) may interfere with learning coping strategies in CBT.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with previous studies, attention to threat on this visual, implicit task seemed to predict limited benefits of CBT [16,18]. As learning is adversely affected by heightened arousal [30], threat perception (and attendant increased arousal) may interfere with learning coping strategies in CBT.…”
Section: Discussionsupporting
confidence: 72%
“…However, included studies used a variety of more or less explicit experimental paradigms. In anxious children, Legerstee and colleagues [16] found that difficulty disengaging from threatening pictures on a dot probe (implicit) task was associated with treatment nonresponse to CBT. Subsequently, they linked normalization of this bias to child response to "stepped care CBT" (an unusually intensive child-and parentfocused intervention) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment responders (N = 26) versus nonresponders (N = 18) were defined as being free from all anxiety disorders diagnosed with the ADIS-C/P-IV at posttreatment assessment (i.e., CSR < 4), consistent with prior studies (e.g., Legerstee et al, 2009;Waters et al, 2012Waters et al, , 2015. Pre-to posttreatment change in SCAS-C and SCAS-P scores were correlated with each dependent variable for anxious children to provide a continuous measure of treatment change.…”
Section: Statistical Analyses Data Screening and Response Definitionsmentioning
confidence: 98%
“…Increasingly, researchers and clinicians working with children who experience clinical levels of anxiety recognize that a focus on changing attentional processing can form an effective component of treatment (e.g. Legerstee et al, 2009). This approach to treatment is summarized in Chapter 13.…”
Section: The Origin and Treatment Of Information Processing Biases Inmentioning
confidence: 99%